FRI0243 Bone Mineral Density in Ankylosing Spondylitis: Meta-Analysis of Retrospective Observational Data from 3420 Subjects. (9th June 2015) - Tatar, Z.; Pereira, B.; Mathieu, S.; Malochet-Guinamand, S.; Guellec, D.; Nocturne, G.; Gossec, L.; Loeuille, D.; Soubrier, M.
Abstract : Background: Osteoporosis (OP) is a frequent complication of ankylosing spondylitis (AS), even in early stages of the disease (1). Assessment of bone mineral density (BMD) remains complicated in these generally male and young patients and consequently, therapeutic indications and issues are not clear (2). Objectives: The objective of this study is to assess the prevalence of low BMD and to detect the predictive clinical or biological parameters of OP in AS patients. Methods: We searched Pubmed, EMBASE and Cochrane databases to perform a meta-analysis of prevalence of low bone mineral density in AS using data from new published observational studies or baseline data from longitudinal studies up to June 2014. The recommendations of PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) were applied (3). The outcome was the BMD measurement assessed with dual x-ray absorptiometry (DEXA) at the lumbar spine or femoral neck in absolute value or T-score. Our comparator population in case-control studies was composed by sex and age-matched healthy subjects. The standard difference in means between AS patients and controls were estimated using DerSimonian and Laird random-effects models. Results: Fourty-six studies were included and concerned 3420 patients with AS. At the femoral neck, the mean BMD was at 0.813 g/cm 2 (IC95% 0.784 – 0.842 g/cm 2 ) with T-score at -1.055 SD (IC95% -1.325-0.785 SD). At the lumbar spine, the mean BMD was at 1.020 g/cm 2 (IC95% 0.999 – 1.040) with T-score at –0.904 SD (IC95% -1.085-0.723). BMD was correlated with age (p=0.02) and AS duration (p=0.007). None statistically significant correlation between BMD and gender (p=0.61), BASDAI (p=0.43), BASFI (p=0.51), CRP (p=0.32), ESR (p=0.64), Body Mass Index (p=0.68) was found. In 21 case-control studies, BMD in AS patients (n=1271) was significantly decreased comparing to control group (n=1858) at the femoral neck (-0.814±0.134; p<0.0001). Nevertheless, this analysis did not reveal significant differences in BMD at the lumbar spine (-0.265±0.186; p=0.156). Conclusions: This first meta-analyses confirmed significant increase of low BMD at the femoral neck in patients with AS compared with age-and-sex-matched healthy controls. This difference disappears at the lumbar spine. Reflection about the OP, vertebral fracture assessment and about the benefit of the OP treatment in AS should be supported and should promote future prospective studies. References: Will R, Palmer R, Bhalla AK et al. Osteoporosis in early ankylosing spondylitis: a primary pathological event? Lancet. 1989 Dec 23-30;2(8678-8679):1483-5. Karberg K, Zochling J, Sieper J et al. Bone loss is detected more frequently in patients with ankylosing spondylitis with syndesmophytes. J Rheumatol. 2005 Jul;32(7):1290-8. Moher D, Liberati A, Tetzlaff J et al; PRISMA Group. Preferred reporting items for systematic reviews and meta-analyses: the PRISMA statement.BMJ. 2009 Jul 21;339:b2535. Disclosure of Interest: None declared